Consolidation, Reforms and Profitability of Deposit Money Banks: Evidence from Nigeria - Bajomo, Olubunmi Adefunke (Archives of Business Research, 2018)
Of all reforms agenda instituted by successive government in Nigeria, the issue of increasing shareholders’ fund to N25 billion and the need to comply before 31st December 2005 generated so much controversy especially among the stakeholders and seemed to have left a lasting impact on the structure of banking in the country. This study aimed to determine the effect of consolidation and resulting reforms on practice and conducts of banks using a profit efficiency function generated by adopting the reduced form of the cost efficiency function that replaces the cost variable with a profit variable via a financial intermediation approach covering the period 2005-2014. The study proves that banking sector reform has a positive effect on industry profitability; with the channels of transmissions being level of capitalization, liquidity and network effectiveness. This study also affirms the structure-conduct-performance (SCP) hypothesis when NIM is used as the dependent variable for Nigerian banking, which indicates that the size and structure of some banks confers some advantages in terms of pricing and product leadership. The study also reinforce the importance of adequate capitalization and liquidity. Finally, volatility resulting from macro-economic policies impacts negatively on bank’s margin as it affects industry perception and attractiveness of the economy to potential investors. Policy initiatives that signals continuing and sustained government focus on maintain macro-economic stability will contribute to growth of banking and as a consequence the real economy.